2013
DOI: 10.1016/j.molimm.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

G-protein signaling modulator-3, a gene linked to autoimmune diseases, regulates monocyte function and its deficiency protects from inflammatory arthritis

Abstract: Polymorphism at the GPSM3 gene locus is inversely associated with four systemic autoimmune diseases, including rheumatoid arthritis and ankylosing spondylitis. G-protein signaling modulator-3 (GPSM3) expression is most pronounced in myeloid cells, in which it targets heterotrimeric G-protein Gαi subunits of chemokine receptors, critical to immune function. To begin to explore the regulatory role of GPSM3 in monocytes, human THP-1 and primary mouse myeloid cells were cultured under stimulus conditions; GPSM3 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 18 publications
4
39
0
Order By: Relevance
“…The location of the Gpsm3 gene within the class III major histocompatibility class locus suggested that AGS4/Gpsm3 is expressed primarily in the immune system, and initial observations from us and others indicated this was indeed the case (Cao et al, 2004;Kimple et al, 2004;Zhao et al, 2010;Schmidt et al, 2012;Giguère et al, 2013). We also discovered AGS4 expression in primary bone marrow-derived dendritic cells and splenocytes (Fig.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The location of the Gpsm3 gene within the class III major histocompatibility class locus suggested that AGS4/Gpsm3 is expressed primarily in the immune system, and initial observations from us and others indicated this was indeed the case (Cao et al, 2004;Kimple et al, 2004;Zhao et al, 2010;Schmidt et al, 2012;Giguère et al, 2013). We also discovered AGS4 expression in primary bone marrow-derived dendritic cells and splenocytes (Fig.…”
Section: Resultssupporting
confidence: 64%
“…A growing number of cellular and physiologic roles have been ascribed to GPR proteins in systems where signal modulation and adaptation are critical for system responsiveness (Bowers et al, 2004(Bowers et al, , 2008Yao et al, 2005Yao et al, , 2006Blumer et al, 2008;Nadella et al, 2010;Regner et al, 2011;Chauhan et al, 2012;Kwon et al, 2012;Giguère et al, 2013;Kamakura et al, 2013;Branham-O'Connor et al, 2014;Singh et al, 2014). The immune system is certainly an area rich in signaling modulation and adaptation and requires dynamic signal processing and spatially integrated G-protein signaling (Cho and Kehrl, 2009;Kehrl et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We are currently testing whether reducing the expression of these proteins impacts phagocytosis. Suggesting that they may have functional roles, myeloid cells from Gpsm3 Ϫ/Ϫ mice migrate less efficiently to Ccl2 and Cx3cl1 than do wild-type mouse myeloid cells (45). Importantly, many of these proteins have additional domains that can interact with other relevant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Some of us have recently described functional studies of G protein signaling modulator-3 (GPSM3), a newly identified signaling regulator with prominent expression in myeloid lineage cells and lower relative expression levels in other hematopoietic lineages as well as non-hematopoietic tissues (16). GPSM3 (a.k.a.…”
mentioning
confidence: 99%
“…AGS4 or G18; Ref. 17,18) possesses two functional "GoLoco motifs" (18) for binding heterotrimeric G protein G␣ i subunits and additionally binds to G␤ subunits during their synthetic pathway toward forming mature G␤␥ dimers (19); these interactions with heterotrimeric G protein subunits are thought to underlie the effects of GPSM3 on chemokine receptor signaling that is critical to the development of inflammatory arthritis (16). More recently, we have described GPSM3 as also interacting directly with the adaptor protein 14-3-3 (20).…”
mentioning
confidence: 99%